Frankly in love - Yoon, David (G. P. Putnam's Sons, 2019)
High school senior Frank Li is caught between his parents' traditional expectations and his own Southern California upbringing. His parents have one rule when it comes to romance: 'Date Korean. But Frank falls for Brit Means, who is smart, beautiful-- and white. Joy Song is in a similar predicament, and they make a pact: they'll pretend to date each other in order to gain their freedom. It seems like the perfect plan, until their fake-dating maneuver leaves Frank wondering if he ever really understood love- or himself- at all. -- adapted from jacket